MicroRNAs at the crossroad of cancer therapeutics: insights from WNT signaling & flavonoids - Gupta, Akanksha; Mehrotra, Arpit; Sood, Abhilasha; Sharma, Bunty; Yadav, Vikas; Kaur, Ginpreet; Sak, Katrin; Satapathy, Shakti Ranjan; Tuli, Hardeep Singh (Frontiers in Molecular Biosciences, 2025)
MicroRNAs (miRNAs) are pivotal post-transcriptional regulators that orchestrate gene expression programs governing cancer initiation, progression, metastasis, and therapeutic resistance. Among their many targets, the WNT signaling pathway, a key driver of malignancy, is tightly controlled by miRNAs, forming intricate feedback loops that shape tumor behavior. Concurrently, flavonoids, naturally occurring plant-derived polyphenols, are emerging as promising anticancer agents that can modulate both WNT signaling and miRNA expression. This review highlights miRNAs as the central regulators of oncogenic signaling, focusing on their dualistic role in cancer biology and their modulation by flavonoids. We explore the mechanistic frameworks underpinning miRNA-WNT interactions and the therapeutic potential of flavonoid-mediated miRNA reprogramming for precision miRNA targeting. Unraveling this regulatory axis offers a promising avenue for developing multi-targeted therapies and personalized cancer treatment strategies.